2023
DOI: 10.1039/d2nr06147c
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling growth and dynamics of liposomes by graphene liquid cell-transmission electron microscopy

Abstract: Liposome is a model system for biotechnological and biomedical purposes spanning from targeted drug delivery to modern vaccine research. Yet, the growth mechanism of liposomes is largely unknown. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…[60][61][62] For example, Jabbari et al recently demonstrated the PISA of a poly(glycerol monomethacrylate)-block-poly(2-hydroxypropyl methacrylate) (PGMA-b-PHPMA) amphiphilic BCP through polymerizing HPMA in water using a PGMA homopolymer as a macro-chain transfer agent for RAFT polymerization. 36 The PISA process was directly visualized through transmission electron microscopy (TEM). Interestingly, irradiation from the electron beam used for imaging in TEM experiments initiated the copolymerization of HPMA, and the PISA into ordered spherical micelles 37 A PCMA macroinitiator was first synthesized through RAFT polymerization which was followed by the polymerization of styrene monomers to induce the self-assembly process.…”
Section: Solution-state Morphology Controlmentioning
confidence: 99%
“…[60][61][62] For example, Jabbari et al recently demonstrated the PISA of a poly(glycerol monomethacrylate)-block-poly(2-hydroxypropyl methacrylate) (PGMA-b-PHPMA) amphiphilic BCP through polymerizing HPMA in water using a PGMA homopolymer as a macro-chain transfer agent for RAFT polymerization. 36 The PISA process was directly visualized through transmission electron microscopy (TEM). Interestingly, irradiation from the electron beam used for imaging in TEM experiments initiated the copolymerization of HPMA, and the PISA into ordered spherical micelles 37 A PCMA macroinitiator was first synthesized through RAFT polymerization which was followed by the polymerization of styrene monomers to induce the self-assembly process.…”
Section: Solution-state Morphology Controlmentioning
confidence: 99%
“…4f shows a TEM image obtained at 200 kV for unstained liposomes in aqueous solution. The quality of this image is remarkable for a specimen that, with few exceptions, 56,57 would normally require the use of staining agents to be observed by LCEM with sufficient contrast. [58][59][60] We observed electron beam induced sample damage progressing on a timescale of about a minute (ESI † Movie S7), which provided us with sufficient time to record many images at a magnification of 22k× with a dose rate of 1.5 electrons Å −2 s −1 .…”
Section: Lcem Studies Of Model Systemsmentioning
confidence: 99%
“…This pointed towards the potential electron beam-induced radical generation from poly GMA-CTA, which initiates HPMA monomer polymerization within a water medium. 36 Diverse systems were investigated using graphene liquid cells, offering comprehensive insights from fabrication to successful sample identification, enabling precise examination of various materials and processes 37 Lastly, leveraging liquid-phase TEM and a U-Net neural network, Chen et al demonstrated real-time imaging of colloidal nanoparticle systems, uncovering otherwise inaccessible nanoscale properties including anisotropic interactions, etching profiles, and kinetic assembly dynamics. 38 Although similar research has been reported, several unresolved questions persist, such as the influence of surfactant molecules on liquid-phase environments, the kinetics of hollow structure dynamics in block copolymer vesicles, and confined self-assembly processes within in situ liquid phases.…”
Section: Introductionmentioning
confidence: 99%